Conditions of The Life Quality – Methodological Remarks - Słaby, Teresa (Economic and Environmental Studies, 2020)
The life quality results from the degree of needs satisfaction, what comes among other from goods and services consumption. The aim of the work is to widespread the outcomes from author’s research attempting to find the determinants of the life quality, using more advanced statistical methods. These methods, on the base of individual distributions and at assumption that ordinal scale is treated as a ratio scale, may widen the analyses of sources conditioning the life quality. With various degree of details, there were presented the results of the life quality statistical modelling. Particular emphasis on usefulness of logit regression model and the use of cumulative probability was applied. Statistical data were drawn from realization of three research projects funded by National Science Centre in 2011-2015.